Researches of open resonant system with the piece of the round wave guide - Кунденко, Николай Петрович; Черенков, Александр Данилович (Eastern-European Journal of Enterprise Technologies, 2012)
Existence of unifrequent fluctuation in resonant system with a piece of a round wave guide is established